THE PATIENTS’ POINT OF VIEW ON THE KNOWLEDGE OF FACTORS, WHICH AFFECT HEALTH IN THE ORAL CAVITY AFTER SURGERY OF CANCER IN THE MOUTH (Zdravstveni glasnik, 2024)
INTRODUCTION: Raising awareness about oral hygiene is essential in every life stage. It is especially important to knowthe risk factors, which affect health in the oral cavity after oral cancer surgery.OBJECTIVE: The objective of this article is to present the patients’ point of view on the knowledge of factors, which affecthealth in the oral cavity after oral cancer surgery.METHODS AND SUBJECTS: A quantitativenon experimental descriptive research was conducted. The questionnairecontaining special questions related to patient sattitude after oral cancer surgery about basic demographics (age, gender,lifestyle, level of education) and questions about the informations obtained by nurses.The research included 112 randomlychosen patients on their follow-up exams after an oral cavity surgery at the Clinic for oral and maxillofacial surgery, UniversityClinicalCenter in Ljubljana.RESULTS: The research showed that most of the interviewed patients smoked, drank alcohol and had a low education. Thepatients know the risk factors after oral cancer surgery, but only a few changed their lifestyle.DISCUSSION AND CONCLUSIONS: Patient education is an integral part of the treatment and should include a discussionof potential oral complications. It is very important that the dental team impress on the patient that optimal oral hygieneduring treatment adequate nutrition and avoiding tobacco and alcohol can prevent or minimize oral complications.